KAJIAN WACANA PUISI HAMIDASE KOKORO KARYA SHUNTARO TANIKAWA: SEBUAH ANALISIS STILISTIKA - Silvia Damayanti (Program Magister Linguistik Universitas Udayana, 2013)
Poetry is a literary work that uses a style that is distinctive. Style in a literary is inportant role to attract and impress the reader. Therefore, the review of literature that emphasizes the beauty of the language style of Stylistics is very important so that the function of literary works can be achieved to the maximum. This study examines the value of aesthetics in poetry Hamidase Stylistics Kokoro Shuntaro Tanikawa's work in a collection of poems titled Suki (2006). Analytic description of the methods and concepts Sudjiman Stylistics (1995) is used in reviewing the language of the poet's style to achieve his idea. Poetry Hamidase Kokoro’s style or stistika poet looks at the ingenuity connotative and denotative use of diction, special words, and words are close to children to beautify and confirmed the meaning of the words and sentences. While the level of the sentence, the poet uses the inversion, interrogative sentence, ellipse, hyperbola, and repetition. The poetry used style of figurative language or words as simple as personofikasi, sinedoke, senestesia, and the paradox is used to increase the aesthetic value of poetry.